Epigenetics in extracellular matrix remodeling and hyaluronan metabolism. (6th November 2014) - Vigetti, Davide; Viola, Manuela; Karousou, Evgenia; Deleonibus, Sara; Karamanou, Konstantina; De Luca, Giancarlo; Passi, Alberto
<x xml:space="preserve">Abstract</x> Cell behavior is determined by both genetic and environmental factors. The cell microenvironment is not only a scene in which various actors play a role, but is itself an active participant, able to influence many cellular responses by binding signaling molecules or by modulating intracellular signaling cascades. Further, extracellular matrix remodeling is a critical step to allow physiological as well as pathological processes. As environmental factors are able to modulate gene expression by epigenetic modifications, this review focuses on new aspects of the regulation of extracellular matrix remodeling enzymes. Moreover, as one of the main components of cell microenvironment is the glycosaminoglycan hyaluronan, novel findings regarding the control of hyaluronan synthesis are discussed in terms of epigenetics and from the post‐translational point of view.